Teacher Roles and Students’ Attitude in “Freedom Writers” Movie - Felicia Regina Prayogo (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
This study is about teacher’s roles and students’ attitudes in Freedom Writersmovie. There two objectives of this study which is to find teacher’s roles and students’ attitudes. The subject of the data are the teacher named Erin Gruwell and the students inside the classroom. The theory used in this study was the theory from Harmer (2001) that explained about teacher’s roles, and the other theory was from Brown (2007) and Wenden (1991) about the students’ attitudes. The findings revealed that teacher’ roles have effect on the attitudes of the students whether the attitude is positive or negative from three components: cognitive, behavioral, and evaluative. Finally, the writer concluded that students’ attitudes depend on the teacher’s roles.